DIGITAL TRANSFORMATION IN THE IMPLEMENTATION OF VILLAGE INFORMATION SYSTEMS IN MEKAR SARI VILLAGE - Try Syeftiani; Yudi; Saadah, Mar Atun; Haris Saputra, Muhammad; Permana, Kurnia (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
The provision of services to rural communities is currently driven by developments in information technology, which require village governments to undertake digital transformation in the implementation of governance and public services. The Village Information System (SSI) is one manifestation of this digital transformation in village government, utilizing technology to support administrative services, data management, and budget transparency. Many previous studies have focused on digital transformation at the central or regional level, but there is limited research that highlights how this process occurs at the village government level as the leading service provider. This study aims to examine the extent to which digital transformation has been implemented in the implementation of the Village Information System (OpenSID) in Mekar Sari Village, Muaro Jambi Regency, and to identify factors that support and hinder this process. The approach used is a qualitative case study method, utilizing data collection techniques such as interviews and document reviews. The findings indicate that the use of OpenSID in Mekar Sari Village has expanded to various service functions, ranging from population data, correspondence, development, assets, to budget transparency. However, technical maintenance of the system remains concentrated in one or two key personnel. This study also reveals that the success of digital transformation in villages is determined by several factors including economic, technical, social, organizational and institutional aspects, as well as legal and regulatory systems. The contribution of this research shows that the success of digital transformation in villages depends not only on the availability of technology, but also on the distribution of operational usage capabilities and the sustainability of institutionalized technical management.